Statins and highly sensitive cardiac troponins: cardiotoxicity or cross-reactivity? - A. M. Chaulin; D. V. Duplyakov (Столичная издательская компания, 2023)
To date, hypolipidemic drugs of the statin group are among the most popular therapeutic agents used for the prevention and treatment of the most common worldwide atherosclerotic cardiovascular diseases (CVD). Therefore, considerable attention of researchers is focused on statins to study the additional effects of these drugs, which is accompanied by the discovery of new mechanisms of action and properties that should be taken into account to optimize the tactics of managing patients with CVD. In addition to the key lipid-lowering effect of statins associated with the inhibition of the ratelimiting enzyme (3-hydroxy-3-methylglutaryl-coenzyme A reductase), researchers report a variety of other properties of these drugs. Important circumstances contributing to the disclosure of new effects of statins are: improvement of research methods, and first of all, their sensitivity and specificity; the discovery of new molecules and molecular pathways that may be affected by statins. In general, the currently established numerous non-lipid effects of statin drugs can be divided into two groups: favorable and side effects, which must be taken into account when managing patients with CVD and comorbid diseases. Thanks to recent studies using modern clinical diagnostic cardiomarkers (highly sensitive cardiac troponins (CT)), molecular genetic and morphological methods, potential cardiotoxic properties of statin group drugs have been identified. Of particular concern are the data on a statininduced increase in the concentration of highly sensitive CT, which are a key and generally recognized criterion for myocardial damage. In this article we discuss possible mechanisms of increasing the concentration of CT and cardiotoxic effects when using statins.